Функціонування жирової тканинини в огрядних хворих на цукровий діабет 2-го типу із синдромом діабетичної стопи - Ларін, О. С.; Горб, Н. В.; Костюк, Т. С.; Малижев, В. О.; Третяк, О. Б.; Черенько, М. С.; Щекатурова, Л. В. (Clinical Endocrinology and Endocrine Surgery, 2010)
Investigation of lipocytokine level in blood serum of patients with type 2 diabetes mellitus and obesity at the first stage of diabetic foot syndrome formation was done. It was found that neuropathic ulcer is accompanied by significant increase of adiponectin and resistin in peripheral blood along with leptin level as in patients with diabetes mellitus without this complication. Changes shown were against a background of acute phase activation that demonstrated by high content of blood interleukin-8, fibrinogen, molecule of adhesion VCAM-1 and decrease of serum albumin quantity.